2013
DOI: 10.1071/mf12296
|View full text |Cite
|
Sign up to set email alerts
|

Managing pollutant inputs from pastoral dairy farming to maintain water quality of a lake in a high-rainfall catchment

Abstract: Abstract.A study ) of a dairy catchment stream entering an oligotrophic lake in an area of very high rainfall (,5 m year À1 ) yielded median concentrations of total nitrogen (TN), total phosphorus (TP), suspended sediment (SS) and Escherichia coli (E. coli) of 0.584, 0.074 and 3.7 g m À3 , and 405/100 mL (most probable number method), respectively. Trend analysis indicated significant (P , 0.01) decreases for TN (À0.08 AE 0.02 g m À3 year À1 ), TP (À0.01 AE 0.005 g m À3 year À1 ) and SS (À0.45 AE 0.14 g m À3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Such long-term cycles in rainfall can result in long-term cycles in transparency and productivity in lakes (Gaiser et al 2009). However, there was no evidence for an increase in rainfall in the catchment affecting Lake Brunner's water quality through increased export of nutrients from the catchment to the lake (our results and Wilcock et al 2013). Therefore, increased intensification of land use through development of dairy farms, coupled with rapid drainage from humping-and-hollowing is likely to be the major cause of increased nutrient concentrations and algal productivity in Lake Brunner.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Such long-term cycles in rainfall can result in long-term cycles in transparency and productivity in lakes (Gaiser et al 2009). However, there was no evidence for an increase in rainfall in the catchment affecting Lake Brunner's water quality through increased export of nutrients from the catchment to the lake (our results and Wilcock et al 2013). Therefore, increased intensification of land use through development of dairy farms, coupled with rapid drainage from humping-and-hollowing is likely to be the major cause of increased nutrient concentrations and algal productivity in Lake Brunner.…”
Section: Discussionmentioning
confidence: 49%
“…The two major streams draining dairy farms contribute 85% of the lake's total P load. A monitoring study (Wilcock et al 2013) has been underway in one of the dairying subcatchments of the Lake Brunner catchment since 2004. Results have shown very high catchment losses of P and N towards the lake that are well above average for intensively farmed land elsewhere in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the effectiveness of the stream fencing, stream bridging, and low‐rate FDE irrigation mitigations are 65, 55, and 29%, respectively. These percentage reductions are averages based on the pooled data, and actual reductions in individual catchments will vary (Wilcock et al, 2013a). …”
Section: Resultsmentioning
confidence: 99%
“…The study by Verburg et al (2013) assessed the relative of these contaminants on an oligotrophic lake (Brunner). Wilcock et al (2013b) found that while trends were decreasing (i.e. improving) for some water-quality contaminants, much of the load of suspended sediment, N and P came from storm flows or was from groundwater that was not encaptured in surface water inflows into the lake.…”
Section: Linking Nutrient Losses To Effects and Management Across Scalesmentioning
confidence: 99%
“…The study by Wilcock et al (2013b) examined catchment sources and pathways for water-quality contaminants. The study by Verburg et al (2013) assessed the relative of these contaminants on an oligotrophic lake (Brunner).…”
Section: Linking Nutrient Losses To Effects and Management Across Scalesmentioning
confidence: 99%